DETEKSI DINI PREEKLAMPSI PADA IBU HAMIL DENGAN IMT (INDEKS MASSA TUBUH), ROT (ROLL OVER TEST) DAN MAP (MEAN ARTERI PRESSURE) - Zakkiyatus Zainiyah; Eny Susanti; Iin Setiawati (P3M Universitas Aisyiyah Surakarta, 2021)
Preeclampsia is a pregnancy hypertension disorder that significantly affects the morbidity and mortality of mothers worldwide. Preeclampsia occurs in 5-7% of all pregnancies and is the leading cause of maternal mortality in developing countries. The purpose of this community devotion to detect preeclampsia in pregnant women with body mass index, ROT (Rool Over Test) and, MAP (Mean Arterial Pressure). Method of community service by conducting a collection of pregnant mothers at local midwives in PMB Sumarti, SST at Kapor village, Burneh, Bangkalan, after that gathered all pregnant women on the day of the specified and explained the purpose of devotion and counseling about preeclampsia in pregnant women, continued weighing weight, measuring height and measured Body Mass Index (BMI), performing blood pressure measurements in pregnant women through ROT and MAP and performed Interviews with providing questionnaires, giving an explanation of preeclampsia early detection on pregnant women, explaining how to prevent and what to do if preeclampsia, monitoring every month until birth. The results of this community devotion from 16 pregnant mothers who performed preeclampsia detection with BMI, ROT, and MAP were obtained 3 (18.75)% positive preeclampsia because there are 2 positive signs after the examination of the sign seen from MAP â‰¥ 90 and BMI â‰¥ 30. The Conclusion that early detection of preeclampsia is necessary to prevent complications during pregnancy, childbirth and postpartum.